The sports performance application of vibration exercise for warm-up, flexibility and sprint speed - Cochrane, D. (European Journal of Sport Science, 2013)
Since the turn of the 21st century, there has been a resurgence of vibration technology to enhance sport science especially for power and force development. However, vibration exercise has been trialled in other areas that are central to athlete performance such as warm-up, flexibility and sprint speed. Therefore, the aim of this review was to attempt to gain a better understanding of how acute and short-term vibration exercise may impact on warm-up, flexibility and sprint speed. The importance of warming up for sporting performance has been well documented and vibration exercise has the capability to be included or used as a standalone warm-up modality to increase intramuscular temperature at a faster rate compared to other conventional warm-up modalities. However, vibration exercise does not provide any additional neurogenic benefits compared to conventional dynamic and passive warm-up interventions. Vibration exercise appears to be a safe modality that does not produce any adverse affects causing injury or harm and could be used during interval and substitution breaks, as it would incur a low metabolic cost and be time-efficient compared to conventional warm-up modalities. Acute or short-term vibration exercise can enhance flexibility and range of motion without having a detrimental effect on muscle power, however it is less clear which mechanisms may be responsible for this enhancement. It appears that vibration exercise is not capable of improving sprint speed performance; this could be due to the complex and dynamic nature of sprinting where the purported increase in muscle power from vibration exercise is probably lost on repeated actions of high force generation. Vibration exercise is a safe modality that produces no adverse side effects for injury or harm. It has the time-efficient capability of providing coaches, trainers, and exercise specialists with an alternative modality that can be implemented for warm-up and flexibility either in isolation or in conjunction with other conventional training methods.